2012
DOI: 10.4028/www.scientific.net/msf.723.460
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Drilling Force during Mandible Drilling Process

Abstract: Drilling procedure is widely used in orthopedic surgery to insert the steel nail to stabilize the bone. However, successful execution of bone drilling requires a high level of dexterity and experience, because the drilling resistance is large and sometimes vibrates violently to even break the slender drill. This paper introduces the study of drill force in different cutting parameters and different bone density. The density of cortical bone is higher than that of cancellous bone, so the drilling force decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
2
1
0
Order By: Relevance
“…Reflecting these factors to our model is required for strict prediction of the magnitude of the drilling force. Nevertheless, we think the present models are reasonable from the viewpoint of approximate correspondence of drilling force between our numerical results and reported experimental data [Wilmes et al, 2008;Wei et al, 2012] described above and practical computational time. We think it is important to establish database which enables dentists to experience relative change in drilling forces due to individual differences and the inner distribution of bone quality and drilling direction of the normal/perforation cases.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Reflecting these factors to our model is required for strict prediction of the magnitude of the drilling force. Nevertheless, we think the present models are reasonable from the viewpoint of approximate correspondence of drilling force between our numerical results and reported experimental data [Wilmes et al, 2008;Wei et al, 2012] described above and practical computational time. We think it is important to establish database which enables dentists to experience relative change in drilling forces due to individual differences and the inner distribution of bone quality and drilling direction of the normal/perforation cases.…”
Section: Discussionsupporting
confidence: 83%
“…Other papers of experimental study for drilling force also support validity of our numerical results. Similar magnitude of drilling force curve which ranged approximately 0.5 N to 2.5 N and its average was 1.3 N (± 0.82 N) for 20 specimens in cancellous area of pig's jawbone was obtained [Wilmes et al, 2008] ratio of drilling forces for cortical region to cancellous region for specimen of human cadaver mandibles was about 2 to 6 times at the same drilling speed [Wei et al, 2012].…”
Section: Discussionsupporting
confidence: 61%
“…Cutting force increases when cutting cortical bone, but it decrease when it reaches cancellous bone due to its reduced hardness. 8 In the study of Alama et al, 9 cutting force and torque were measured in ultrasonically assisted drilling of cortical bone. In the research of Pirtini and Lazoglu, 10 ultrasonically assisted drilling was found to decrease the drilling force and torque in half.…”
Section: Introductionmentioning
confidence: 99%